Skin Burn by Termal Mattress - A Therapeutic Approach - Gorczak, Rochelle; Valandro, Marilia Avila; Carvalho, Isabella Michels; Coelho, Ana Carolina (Acta Scientiae Veterinariae, 2021)
Background: Burns are caused by a direct or indirect action of heat on an organism, compromising the functional integrity of the skin. Hypothermia is a common intercurrence in animals during the transoperative period; thermal mattresses are used to maintain the animal’s body temperature, but inappropriate use can cause the patient’s skin to burn. In humans, burns are quite common; however, in veterinary medicine, they are infrequent. The aim of this study was to describe a case of accidental burn in a canine caused by a thermal mattress, emphasizing wound treatment and analgesia used. Case: A 12-year-old male canine without defined breed weighing 15 kg underwent an emergency exploratory laparotomy due to rupture of a spleen mass and presented with intercurrence hypothermia during the anesthesia procedure, which was controlled using a thermal mattress. Ten days after the surgical procedure, he developed a skin lesion with erythema, suffusion, and necrosis, evolving skin displacement along the entire back with a lot of pain which was possibly caused by the use of a thermal mattress in the transoperative procedure. The intuited analgesic treatment involved the use of numerous and different drugs, including Methadone (0.3 mg/kg, QID, SC), Dipyrone (25 mg/kg, TID, IV), and Ketamine (0.5 mg/kg, TID, SC) (during hospitalization), as well as Tramadol (4 mg/kg, TID, PO) and Dipyrone (25 mg/kg, TID, PO) after medical release as support therapy. For the wound treatment, calcium alginate was initially used daily and subsequently changed for daily application of dermisana oil. The patient followed up weekly for approximately two months for wound monitoring as well as adjustments to the drug therapy. The would almost completely healed, but the patient showed a significant worsening in the general clinical condition correlated with the neoplasm that he had, and the owner and clinical staff of the veterinary hospital opted for euthanasia. Discussion: Hypothermia should be avoided as much as possible during anesthesia, as the body’s temperature is very important in homeostasis, in addition to being able to change the pharmacokinetics and pharmacodynamics of some drugs. The use of a thermal mattress to avoid hypothermia during the intraoperative period is a common and useful tool in veterinary routine, but should be used with caution and constant monitoring of the animal under general anesthesia to avoid skin burns which are not immediately noted. When diagnosed, the treatment should aim for wound healing and provide analgesia. Different pharmacological approaches can be used for this purpose, including topical therapies with different products that provide wound healing and regard to analgesia can be used for association of non-steroidal anti-inflammatory drugs such as meloxicam, opioids like morphine and tramadol, and N-Methyl-D-aspartate (NMDA) blockers like ketamine for analgesia. Burn treatment is difficult but can have a favorable prognosis. In the present report, the conservative wound management using sodium alginate and dermisana oil almost completely cured the wound, and the canine responded positively to the analgesic protocol instituted with the association of different drugs. It is still important to highlight the attendance and commitment of the owner in the proposed treatment, as euthanasia, in this case, was due to the comorbidity presented by the patient.